Agente Recomendador Híbrido de Objetos de Aprendizaje - Solís-Céspedes, Jacqueline (Instituto Tecnológico de Costa Rica, 2014)
In this thesis research we present the model and prototype of a Hybrid Recommender Agent to suggest learning resources for a course from applying data mining techniques. This recommender takes as inputs the Instructional Design and Learning Styles Theory to perform the search, selection and recommendation of learning objects on a repository in the cloud.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2014.
Keywords: Prototipo; Datos; Minería de datos; Diseño instruccional; Técnicas de aprendizaje; Teorías